2002
DOI: 10.5194/angeo-20-1943-2002
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of ion energization at 1700 km in the auroral region

Abstract: Abstract. We present a comprehensive overview of several potentially relevant causes for the oxygen energization in the auroral region. Data from the Freja satellite near 1700 km altitude are used for an unconditional statistical investigation. The data are obtained in the Northern Hemisphere during 21 months in the declining phase of the solar cycle. The importance of various wave types for the ion energization is statistically studied. We also investigate the correlation of ion heating with precipitating pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Gurnett and Frank, 1977;Kintner et al, 2000;Wahlund et al, 2003) and are often associated with local ion energization (e.g. André et al, 1998;Hamrin et al, 2002;Bouhram et al, 2003aBouhram et al, , 2003b. Several studies with Interball-1 (see Savin et al, 2004, and references therein) focus on the boundary between cusp and magnetosheath.…”
Section: Introductionmentioning
confidence: 99%
“…Gurnett and Frank, 1977;Kintner et al, 2000;Wahlund et al, 2003) and are often associated with local ion energization (e.g. André et al, 1998;Hamrin et al, 2002;Bouhram et al, 2003aBouhram et al, , 2003b. Several studies with Interball-1 (see Savin et al, 2004, and references therein) focus on the boundary between cusp and magnetosheath.…”
Section: Introductionmentioning
confidence: 99%
“…In the cusp/cleft and at the poleward edge of the auroral oval, recent statistical studies using FAST (Lund et al, 2000) and Freja (Hamrin et al, 2002) satellite data reported a strong link between ion conic events and enhancements of the broad-band extremely low frequency (BBELF) turbulence. Its spectral shape may be modeled by a power law profile versus frequency (Kintner, 1976), as parametrized by a spectral index α.…”
Section: Adiabatic Transportmentioning
confidence: 99%
“…We use the OP global empirical model of broadband aurora [ Newell et al , 2009], statistical patterns of O + outflow from Chaston et al [2007], correlations between heated O + and resonant waves of Hamrin et al [2002a, 2002b] and averages of broadband electric fields of Kasahara et al [2001] as proxies for transverse wave heating in the altitude range between the DMSP and Polar data sets from 850 km to ∼6000 km. Newell et al [2009] used their empirical model of broadband aurora at 850 km [ Newell et al , 2009, Figure 4a] to argue that these broadly peaked down flowing electron distributions are associated with Dispersive Alfven Waves (DAWs) operating at higher altitudes.…”
Section: Proxies Of Energization Mechanismsmentioning
confidence: 99%
“…'s results, it is reasonable to assume that the locations of enhanced ion outflow and the “% Alfvén Wave Driven” shown apply reasonably well to the lower activity levels reported here, though with a reduction in the percent driven by Alfvén waves in the midnight sector (C. Chaston, private communication, 2011). At altitudes below FAST, Hamrin et al [2002a, 2002b] have used observations on the Freja spacecraft (∼1700 km) to show that the existence of O + outflows and waves, which transversely heat O + , are highly correlated. Hamrin et al similarly found a greater occurrence rate of heated O + and resonant waves near midnight.…”
Section: Proxies Of Energization Mechanismsmentioning
confidence: 99%